O poder da política e a política do poder - Grohmann, Luís Gustavo M. (Revista de Desenvolvimento e Políticas Públicas, 2017)
The paper reflects on the processes of political reform in Brazil, its proposals and the institutional changes after 1988. It considers especially the period that preceded the impeachment of President Dilma until the first year of the Temer Government. Its normative axis is the constitution and maintenance of democratic processes. Reaches perspectives for Brazilian political development, focusing on the process of political representation, forces in competition and elections for 2018.